Parametric computational study on butterfly-shaped hysteretic dampers - FARZAMPOUR, Alireza; EATHERTON, Matthew Roy (Frontiers of Structural and Civil Engineering, 2019)
A parametric computational study is conducted to investigate the shear yielding, flexural yielding, and lateral torsional buckling limit states for butterfly-shaped links. After validating the accuracy of the finite element modeling approach against previous experiments, 112 computational models with different geometrical properties were constructed and analyzed including consideration of initial imperfections. The resulting yielding moment, corresponding critical shear force, the accumulation of plastic strains through the length of links as well as the amount of energy dissipated are investigated. The results indicate that as the shape of the butterfly-shaped links become too straight or conversely too narrow in the middle, peak accumulated plastic strains increase. The significant effect of plate thickness on the buckling limit state is examined in this study. Results show that overstrength for these links (peak force divided by yield force) is between 1.2 and 4.5, with straight links producing larger overstrength. Additionally, proportioning the links to delay buckling, and designing the links to yield in the flexural mode are shown to improve energy dissipation.